Direct silanization of zirconia for increased biointegration. (December 2016) - Caravaca, Carlos; Shi, Liu; Balvay, Sandra; Rivory, Pascaline; Laurenceau, Emmanuelle; Chevolot, Yann; Hartmann, Daniel; Gremillard, Laurent; Chevalier, Jérôme
Graphical abstract: Abstract: High-performance bioinert ceramics such as zirconia have been used for biomedical devices since the early seventies. In order to promote osseointegration, the historical solution has been to increase the specific surface of the implant through roughness. Nevertheless these treatments on ceramics may create defects at the surface, exposing the material to higher chances of early failure. In zirconia, such treatments may also affect the stability of the surface. More recently, the interest of improving osseointegration of implants has moved the research focus towards the actual chemistry of the surface. Inspired by this, we have adapted the current knowledge and techniques of silica functionalization and applied it to successfully introduce 3-aminopropyldimethylethoxy silane (APDMES) directly on the surface of zirconia (3Y-TZP). We used plasma of oxygen to clean the surface and promote hydroxylation of the surface to increase silane density. The samples were extensively characterized by means of X-ray photoelectron spectroscopy (XPS) and contact angle, mechanically tested and its cytotoxicity was evaluated through cell adhesion and proliferation tests. Additionally, aging was studied to discard negative effects of the treatment on the stability of the tetragonal phase. No adverse effect was found on the mechanical response of treated samples. In addition, plasma-treated samples exhibited an unexpectedly higher resistance to aging. Finally, silane density was 35% lower than the one reported in literature for silica. However cells displayed a qualitatively higher spreading in opposition to the rounder appearance of cells on untreated zirconia. These results lay the foundations for the next generation of zirconia implants with biologically friendlier surfaces. Statement of Significance: The use of zirconia-based ceramics in biomedical devices is broad and well accepted, especially in dental implants. However, they do not bond naturally to bone, therefore to ensure fixation surgeons typically rely on roughness at different scales, or on cements. Alternatively in this work we present a new perspective of surface modification through chemistry to enhance the interaction between surface and biological environment, without the downsides of roughness. This surface treatment is proposed for zirconia, which allowed a direct silanization of its surface and a higher cell attachment. The results of this research may open the possibility for the next generation of bioinert ceramic implants with more advanced tailored surfaces for increased osseointegration.